Cytochrome P450 expression in mouse brain: specific isoenzymes involved in Phase I metabolizing system of porphyrinogenic agents in both microsomes and mitochondria - Lavandera, Jimena Veronica (2015)
Brain cytochrome P450 (CYP) metabolizes a variety of drugs to produce their pharmacological effects within the brain. We have previously observed that porphyrinogenic agents altered CYP levels in brain. The aim of this work was to further study the involvement of mice brain mitochondrial and microsomal Phase I drug metabolizing system when porphyrinogenic agents, such as Enflurane, isoflurane, allylisopropylacetamide, veronal, ethanol, and Griseofulvin were administered. To this end, CYP2E1, CYP2B1, and CYP3A4 expression were measured. NADPH cytochrome P450 reductase (CPR) expression was also determined. Western Blots were performed in microsomes and mitochondria of whole brain. Some of the drugs studied altered expression mainly in microsomes. Chronic Isoflurane augmented mitochondrial isoform, although this anaesthetic diminished microsomal expression. Ethanol and topical Griseofulvin affected expression in microsomes but not in mitochondria. CYP2E1 mitochondrial activity was induced by acute Enflurane; while the activity of the microsomal protein was enhanced in alcoholised animals. Ethanol also induced CYP2E1 expression in microsomes, although Isoflurane provoked opposite effects in mitochondria and microsomes. Expression of CPR was also induced. Several reports support an emergent role of CYP enzymes in the pathogenesis of neurological disorders, so CYP response in brain could be one of the multiples factors influencing porphyria acute attacks.